18F-FLT PET imaging of cellular proliferation in pancreatic cancer. (March 2016) - Lamarca, Angela; Asselin, Marie-Claude; Manoharan, Prakash; McNamara, Mairéad G.; Trigonis, Ioannis; Hubner, Richard; Saleem, Azeem; Valle, Juan W.
Highlights: There is a potential for integrating other imaging modalities in the management of pancreatic cancer. Standard uptake values from 18 F-FLT PET images have been shown to correlate with cellular proliferation in some malignancies. 18 F-FLT PET in GI malignancies is limited by high physiologic radiotracer uptake in surrounding normal tissues and liver. 18 F-FLT PET has higher specificity but lower sensitivity compared to 18 F-FDG PET for measurement of cellular proliferation. Dynamic imaging with 18 F-FLT PET allows an improved understanding of treatment effects and detection of liver metastases. Abstract: Pancreatic ductal adenocarcinoma is known for its poor prognosis. Since the development of computerized tomography, magnetic resonance and endoscopic ultrasound, novel imaging techniques have struggled to get established in the management of patients diagnosed with pancreatic adenocarcinoma for several reasons. Thus, imaging assessment of pancreatic cancer remains a field with scope for further improvement. In contrast to cross-sectional anatomical imaging methods, molecular imaging modalities such as positron emission tomography (PET) can provide information on tumour function. Particularly, tumour proliferation may be assessed by measurement of intracellular thymidine kinase 1 (TK1) activity level using thymidine analogues radiolabelled with a positron emitter for use with PET. This approach, has been widely explored with [ 18 F]-fluoro-3′-deoxy-3′-l -fluorothymidine ( 18 F-FLT) PET. This manuscript reviews the rationale and physiology behind 18 F-FLT PET imaging, with special focus on pancreatic cancer and other gastrointestinal malignancies. Potential benefit and challenges of this imaging technique for diagnosis, staging and assessment of treatment response in abdominal malignancies are discussed.